Teks Pesantren dan Budaya Damai - Cipto Sembodo (TASAMUH: Jurnal Studi Islam, 2015)
This article tries to discribe the value of Pesantren tradition. Who alwasys be more fiqih oriented than the other. This article gives a solution about the normative values in Pesantren. The value of usul fiqih in Pesantren must be important than figih oriented mind. So the paradigm of usul fiqih must be discoured on the fiqih. Figih oriented only brings to closed minded than usul fiqih. Usul fiqih brings to open minded in the world.